Hipersuperfícies conformemente euclidianas com curvatura média ou escalar constante - Rei Filho, Carlos Gonçalves do (Universidade Federal de São Carlos, 2016)
In this work we study conformally flat hypersurfaces f: M3 ^ Q4(c) with three distinct principal curvatures in a space form with constant sectional curvature c, under the assumption that either its mean curvature H or its scalar curvature S is constant. In case H is constant, first we extend to any c G R a theorem due to Defever when c = 0 and show that there is no such hypersurface if H = 0. Our main results are for the minimal case H = 0. If c = 0, we prove that f (M3) is an open subset of a generalized cone over a Clifford torus in an umbilical hypersurface Q4(c) C Q4(c), c > 0, with c > c if c > 0. For c = 0, we show that, besides the cone over the Clifford torus in S3 C R4, there exists precisely a one-parameter family of (congruence classes of) minimal isometric immersions f: M3 ^ R4 with three distinct principal curvatures of simply-connected conformally flat Riemannian manifolds. Assuming S to be constant, we only study the case c = 0. We prove that f (M3) is an open subset of a cylinder over a surface of nonzero constant Gauss curvature in R3.
Keywords: Hipersuperfícies conformemente euclidianas; Hipersuperfícies mínimas; Curvaturas principais distintas; Conformally flat hypersurfaces; Minimal hypersurfaces; Distinct principal curvatures; Constant mean; CIENCIAS EXATAS E DA TERRA::MATEMATICA; CIENCIAS EXATAS E DA TERRA::MATEMATICA::GEOMETRIA E TOPOLOGIA